DETERMINANTS OF ENERGY DISCLOSURE STAKEHOLDER THEORY PERSPECTIVE - Christian Lucky Thunggono; Aminah; Khairudin; Indrayenti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Energy disclosure is a form of corporate social responsibility related to the energy it uses. This form of responsibility is described in the annual report or sustainability report. The purpose of this study is to empirically examine the impact of profitability, leverage, managerial ownership, and directors on energy disclosure. The sample selection in this study was carried out through  the purposive sampling method, which resulted in 120 data samples from non-cyclical consumer sector companies  listed on the IDX for the 2021-2022 period. The test was conducted using the SPSS 18 tool with multiple linear regression data analysis techniques. The results showed that profitability and directors  had a significant positive effect, leverage  had a significant negative impact, and managerial ownership had a significant negative impact.